Soviet Biological Exploration in Antarctic Seas - Gruzov, Evgeni (ARCTIC, 1968)
. The 11th Soviet Antarctic Expedition was the first in Soviet antarctic research to employ aqualungs in biological exploration. Such explorations were conducted from mid-December to March, during the antarctic summer 1966-67. The special methods we employed were determined by the peculiar nature of our hydrobiological research. Instead of exploring the expanses of the ocean bottom, as had been the practice of all foregoing expeditions, we confined our observations to a limited area of shallow sea between the Haswell Islands near the Mirny Observatory. Lightweight diving apparatus permitted us to observe animals in their natural environment, discover the nature of submarine communities, and collect specimens of the flora and fauna. All together, 144 dives were made. . Three months' work yielded extensive collections which were brought to the Zoology Institute of the U.S.S.R. Academy of Sciences in Leningrad. However, the main significance of the expedition was the opportunity afforded to study the communities of animals and the regularities of their distribution throughout the sea depths. Few such observations have been made in Antarctica. .